Measurement of Compliance With New York City’s Regulations on Beverages, Physical Activity, and Screen Time in Early Child Care Centers - Lessard, Laura (Centers for Disease Control and Prevention, 2014)
INTRODUCTION: Policy interventions designed to change the nutrition environment and increase physical activity in child care centers are becoming more common, but an understanding of the implementation of these interventions is yet to be developed. The objective of this study was to explore the extent and consistency of compliance with a policy intervention designed to promote nutrition and physical activity among licensed child care centers in New York City. METHODS: We used a multimethod cross-sectional approach and 2 independent components of data collection (Center Evaluation Component and Classroom Evaluation Component). The methods were designed to evaluate the impact of regulations on beverages served, physical activity, and screen time at child care centers. We calculated compliance scores for each evaluation component and each regulation and percentage agreement between compliance in the center and classroom components. RESULTS: Compliance with certain requirements of the beverage regulations was high and fairly consistent between components, whereas compliance with the physical activity regulation varied according to the data collection component. Compliance with the regulation on amount and content of screen time was high and consistent. CONCLUSION: Compliance with the physical activity regulation may be a more fluid, day-to-day issue, whereas compliance with the regulations on beverages and television viewing may be easier to control at the center level. Multiple indicators over multiple time points may provide a more complete picture of compliance — especially in the assessment of compliance with physical activity policies.